Practice of Cancellation of Agricultural Land Lease Agreement Unilaterally in Islamic Law in Sejangkung Hamlet Parit Raja Village Sejangkung District - Anong Rusda; Zarul Arifin (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Leasing agricultural land at this time seems to have become a necessity for the community, especially for those who do not have agricultural land to work on. Like what the people of Dusun Sejangkung did, who rented agricultural land to meet their daily needs. Leasing activities carried out by the community do not always run smoothly, sometimes there are several problems that arise during the rental process, one of which is the unilateral cancellation of the rental relationship due to the sale of the leased object by the owner at the time of planting without the knowledge of the tenant. It becomes a big question whether this kind of activity is allowed or not in Islamic law. The purpose of this study was to find out how the practice of unilaterally canceling agricultural land rental relations in Islamic law in Sejangkung Hamlet, Parit Raja Village, Sejangkung District. This type of research uses qualitative research that is field research (Field Research) with empirical sociological research methods, namely examining phenomena that occur in the field related to community behavior and seeing facts that occur in the field, namely in the community in Sejangkung Hamlet. To obtain data, researchers used interview and observation guidelines. Based on the results of the study that the cancellation of the agricultural land lease relationship unilaterally in Islamic law in Sejangkung Hamlet in terms of the pillars of ijarah and the conditions of ijarah have been fulfilled, but from the ijarah principle there are several principles that are not fulfilled, namely the principle of al-is (justice), the principle of al-ta'awun (mutual benefit). The lease agreement can end if there is a justifiable reason that requires the ijarah contract to be cancelled, the end of the agreed ijarah contract and if one of the parties is old.